1983
DOI: 10.1139/v83-384
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution enthalpies of NaI in binary mixtures of water with aliphatic alcohols and methylcellosolve at 298.15 K. Enthalpic pair interaction coefficients of NaI–nonelectrolyte in water solution

Abstract: The enthalpy of solution, AH,,,,. of NaI in methanol + water, ethanol + water, 11-propanol + water, ~sopropanol + water, and methoxyethanol + water at all compositions and AH,,,, of NaI in s-butanol + water and ter-t-butanol + water from 0 to 5 mol% alcohol was measured.The NaI-nonelectrolytc pair interaction enthalpies were determined and correlated with the functions describing some properties of the nonelectrolyte. A functional group additivity concept, introduced by Savage and Wood for non-ionic solutes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 24 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…1 enthalpy of NaCl solution in water mixtures of isopropanol, 2-methoxyethanol, 2-ethoxyethanol shows a maximum analogous to that observed in other wateralcohol mixtures hitherto analyzed (4,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). It is generally accepted that this maximum is connected with the structuremaking or -stabilizing effect of the added alcohol on water (24)(25)(26)(27)(28).…”
Section: Enthalpy Of Solutionsupporting
confidence: 53%
See 2 more Smart Citations
“…1 enthalpy of NaCl solution in water mixtures of isopropanol, 2-methoxyethanol, 2-ethoxyethanol shows a maximum analogous to that observed in other wateralcohol mixtures hitherto analyzed (4,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). It is generally accepted that this maximum is connected with the structuremaking or -stabilizing effect of the added alcohol on water (24)(25)(26)(27)(28).…”
Section: Enthalpy Of Solutionsupporting
confidence: 53%
“…[6] for h,, values for nine nonelectrolytes having in their molecule the distinguished groups (methanol, ethanol, propanol, isopropanol, s-butanol, 2-methoxyethanol, 2-ethoxyethanol, THF, dioxane) the group contributions collected in Table 3 were calculated. Table 3 also shows analogous group contributions referring to (Na+ + I-)-nonelectrolyte systems described in a previously cited work (4). In order to compare both data series, values concerning the (Naf + I-)-nonelectrolyte systems were recalculated taking additional It,, coefficients for (Na' + I )-THF and (Na+ + I-)-2-ethoxyethanol(36) pairs.…”
Section: Enthalpic Pair Interaction Coeficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the negative h xy values observed for non-electrolytes with strong polar group in their molecule like: formamide (FA), acetamide (AA), urea, DMSO, reflect the advantage of the exothermic effect of direct interactions. It was found that the enthalpic pair interaction coefficients for the NaI-non-electrolyte pairs in water were linearly correlated with functions describing some properties of the non-electrolytes, such as molecular polarizability (a), or DimrothReichardt polarity parameter (E T ) [12]. However, these correlations hold only for groups of related compounds.…”
Section: Analysis Of Dissolution or Transfer Enthalpies In Binary Solmentioning
confidence: 99%
“…These deviations are, to a large extent, a result of strong interactions among the molecules of both co-solvents leading to the changes of mixture structure with the change of composition. Figure 1 presents the standard dissolution enthalpies of NaI in the mixtures of water with aliphatic alcohols as a function of the mole fraction of alcohol [1,2] The curves representing the enthalpy of solution exhibit maxima at a low alkanol content. It is generally accepted that these maxima are related to a structure-promotion or a structure-stabilizing effect of added alkanol on water, due to the hydrophobic hydration of the alcohol alkyl group.…”
Section: Enthalpies Of Solution and Enthalpies Of Transfermentioning
confidence: 99%